Alterations in regional myocardial deformation assessed by strain imaging in cardiac amyloidosis. Issue 12 (7th September 2016) - Lo, Queenie; Haluska, Brian; Chia, Ee‐May; Lin, Ming‐Wei; Richards, David; Marwick, Thomas; Thomas, Liza
Abstract : Background: Cardiac amyloidosis results in increased left ventricular (LV) wall thickness and diastolic dysfunction (DD). Strain measurements using velocity vector imaging (VVI) may further characterize myocardial dysfunction. Methods: A total of 43 AL amyloidosis patients were compared to age‐matched normals and hypertensive patients (HT). Subgroup analysis within the amyloid group was performed based on LV wall thickness (≤14 mm, >14 mm) and diastolic dysfunction (DD) (Group 1: normal and impaired relaxation, Group 2: pseudonormal, Group 3: restrictive). LV strain (longitudinal, circumferential, and radial strain (S) and strain rate [Sr]) were measured using velocity vector imaging (VVI). Results: Increased LV wall thickness and DD were observed in the amyloid group. Global longitudinal (−13.9±4.1% vs −16.7±3.8%; P =.002) and radial (27.4±13.4% vs 38.8±15.7%; P <.001) strain were lower in the amyloid group vs normal controls, while circumferential strain was similar. Segmental analysis demonstrated reduced mid‐ and basal segmental strain with relative sparing of apical segments in the amyloid group. Reduced longitudinal and radial strain, with preserved circumferential strain, were observed in patients with wall thickness >14 mm; however, circumferential strain was also altered when severe DD (restrictive filling) was present. Conclusion: Reduction in longitudinal and radial S and Sr was evident using VVI strain analysis in amyloidosis, with segmental heterogeneity in longitudinal S. There was relative preservation of circumferential strain, which was reduced only in patients with severe DD.